3D Printed Hemispherically Radiating Antenna for Broadband Millimeter Wave Applications - Engel, Lukas; Khouri, Danti; Lomakin, Konstantin; Hofmann, Andreas; Kleinlein, Micha; Ullmann, Ingrid; Vossiek, Martin; Gold, Gerald (IEEE Open Journal of Antennas and Propagation, 2023)
Nowadays, additive manufacturing provides far-reaching possibilities for use in radio frequency components. In addition to almost unlimited freedom of design as compared to conventional manufacturing, the absence of further assembly steps is a key aspect of 3D printing. In this paper, a 3D printed monolithic antenna for millimeter wave-sensing applications is presented with a full hemispherical coverage. The antenna is designed as an ensemble of a waveguide horn antenna and a differentially fed dipole antenna. The slotted waveguide approach was utilized to improve the manufacturing quality on the waveguide inside. The influence of two optimized antenna elements, a metal plane, and a cut-out window, on the beam pattern is comprehensively investigated. A huge half power beam width of 142° in both directions, elevation and azimuth, is presented at 79 GHz and a boresight gain of 4.7 dBi was measured. The beam pattern in the frequency range from 76 to 81 GHz is studied in greater detail, where a half power beam width of at least 112° is achieved. Due to the −10 dB matching capability bandwidth of over 28 GHz, the antenna is also suitable for extremely broadband applications with a −5 dB angular width of better than 100°. Furthermore, the system design describes how to integrate the antenna into hybrid circuit designs and the manufacturing tolerances are examined. The antenna offers attractive possibilities for millimeter wave-sensing applications in the area of assisted living and industrial monitoring, especially whenever blind spots have to be avoided.<br

Additively manufactured antennas based on slotted ridged waveguides for 77 GHz MIMO radar applications - Kleinlein, Micha; Lomakin, Konstantin; Rösner, Felix; Hofmann, Andreas; Sippel, Mark; Gold, Gerald (2023 IEEE Conference on Antenna Measurements and Applications (CAMA), 2023)
In this work an additively manufactured waveguide antenna array for automotive radar applications is presented. The antenna is based on a slotted single ridged waveguide design with four radiating elements in the elevation plane. This allows for a λ 0 /2 spacing at 76 to 77 GHz, which is desirable to minimise azimutal angular ambiguities in automotive radar applications. The influence of adjacent surfaces close to the radiating slots in the azimutal field of view (FoV) is evaluated based on simulations and measured prototypes, especially demonstrating its role when extending the FoV towards ±70°. Furthermore, the impact on mutual coupling with neighboring antenna elements and the interaction of several channels with the arrays’ cover are evaluated based on a 4x4 channel array prototype, which is also manufactured and measured. The entire antenna arrays are manufactured monolithically with a photopolymer based 3D-printing process and subsequently electroplated in cooperation with Golden Devices Gmb
Keywords: Antenna measurements; Slot antennas; Surface waves; Three-dimensional printing; Radar antennas; Loss measurement; Radar applications

A Drone-Based 0.7-4.7 GHz FMCW Radar System for High-Resolution Exploration of Subsurface Glacier Structures - Stelzig, Michael; Benedikter, Andreas; Kleinlein, Micha; Haberberger, Niklas; Krabbe, Lena; Lomakin, Konstantin; Braun, Matthias; Krieger, Gerhard; Vossiek, Martin (2023 IEEE International Radar Conference (RADAR), 2023)
A majority of the studies on subglacial structure mapping and imaging have relied on low-frequency ground penetrating radar (GPR) systems. In particular, mapping alpine glaciers using surface-based high-resolution radar sensors poses a considerable threat to the operators due to crevasses or avalanches; this can be avoided by deploying an unpiloted aerial vehicle (UAV)-based radar sensor. Herein, we present an ultrawideband (UWB) bistatic frequency-modulated continuous-wave (FMCW) GPR for operation on a UAV. By using a UAV equipped with ultrawideband and extremely lightweight additively manufactured horn antennas at a bandwidth of 4GHz between 0.7 GHz and 4.7 GHz we acquired ultra-high-resolution images of the upper firn layers of an alpine glacier. The acquired measurements at the Jungfraufirn, Switzerland illustrate the out-standing performance of the overall system and its applicability in glaciological research.<br
Keywords: Ground penetrating radar; Horn antennas; Radar; Bandwidth; Radar imaging; Radar antennas; Autonomous aerial vehicles; Unpiloted Aerial Vehicle; Frequency-Modulated Continuous-Wave Radar; Horn Antenna; Subsurface Imaging; Glacial Exploration; Ground Penetrating Radar

SLS-Printed E-Band Waveguides and the Impact of Surface Roughness - Hofmann, Andreas; Lomakin, Konstantin; Kleinlein, Micha; Bader, Tobias; Sippel, Mark; Gold, Gerald (European Microwave Conference (EuMC), 2023)